Pengaruh Kepemimpinan, Motivasi Dan Komunikasi Terhadap Kinerja Karyawan (Studi Pada Usaha Dagang Sumber Rejeki Konang Bangkalan) - Moh. Romli; Abdul Kodir Djaelani; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine the effect of leadership, motivation and communication on employee performance. The purpose of this research is the employees of UD Sumber Rejaki Konang Bangkalan. The sampling method used is a saturated sampling technique. it can be concluded that leadership has no significant effect on employee performance, which partly comes from changes in motivation that affect employee performance. While the part that comes from the communication variable has an effect on employee performance. Consistent with the results of the research being tested, it proves that changes in Leadership, Motivation and Communication that are consistent with the results of tests carried out together have an impact on customer satisfaction. Keywords: Leadership, Motivation, Communication and Employee Engagement